Potentiometric Determination of Mebeverine Hydrochloride Using Imprinted Molecular Polymer in PVC Matrix Membrane - Al-Bayati, Yehya Kamal; Al Khafaji , Inas Hasan (Iraqi Journal of Science, 2022)
Four molecular imprinted polymer (MIP) membranes for Mebeverine.HCl (MBV.HCl) were prepared based on PVC matrix. The imprinted polymers were prepared by polymerization of 2-acrylamido-2-methyl-1-propane sulphonic acid (AMPS) as monomer, pentaerythritoltriacrylate (PETRA) as a cross linker ,benzoyl peroxide (BPO) as an initiator and mebeverine as a template. Four different types of plasticizers of different viscosities were used and the electrodes were fully characterized in terms of plasticizer type, response time, lifetime, pH and detection limit.The MBV-MIP electrodes exhibited Nernstian response in concentration range from 1.0×10-6 to1.0×10-1 M with slopes of 13.98, 19.60, -20.43 and 19.01 mV/ decade. The detection limit and quantification are found to be 4×10-6, 3× 10-6, 2× 10-5and 1.2× 10-6 M ,respectively. Interference study for inorganic cations and amino acids was also studied. The best electrode based tris (2-ethyl hexyl) phosphate plasticizer was applied successfully for potentiometric determination of mebeverine in commercial tablets. Excellent average recovery obtained by potentiometric methods was about 102.26% which is in good agreements with British Pharmacopoeia.